The Use of Media With English Lyrics To Improve The Mastery Of English Grammar In High School Students State 3 Samarinda - Sutiati, Sutiati (PT Literasi Nusantara Publisher, 2022)
This study aims to improve English grammar skills for high school students state 3 Samarinda. This study uses a classroom action research design that was carried out at SMA Negeri 3 Samarinda for students of class XI IPS. The results showed that there was a significant increase in students' English grammar mastery as indicated by the data of an increase in students' English grammar mastery. The score of English grammar after the classroom action research was conducted, the percentage improvement was 13%. So, it can be concluded that the song media with English lyrics can improve students' grammar mastery.